Anaesthetic management of cerebral arteriovenous malformation hemorrhage during pregnancy: A case series. Issue 5 (3rd February 2023) - Ji, Yong; Liang, Yi; Liu, Bin; Wang, Yaxin; Li, Ling; Liu, Yan; Feng, Yifan; Dong, Nuo; Xiong, Wei; Yue, Hongli; Jin, Xu
Abstract : Rationale: There is no clear consensus guidance for anesthesiologists on how to manage patients with cerebral arteriovenous malformation (cAVM) rupture and hemorrhage during pregnancy who need craniotomy. Our objective was to review the anesthesia management of pregnant women who underwent resection of cAVM at our institution and to provide opinions and suggestions. Patient concerns: Herein, we report of 3 patients with cAVM rupture and hemorrhage during pregnancy who underwent neurosurgery at the 22nd, 28th, and 20th weeks of pregnancy. Diagnoses: All 3 patients were admitted to the emergency department of our hospital due to sudden symptoms. Subsequently, their head imaging results confirmed the rupture and hemorrhage of cAVM. The rupture and hemorrhage of cAVM during pregnancy has a low incidence and high mortality, which seriously endangers the safety of the mother and fetus. For this emergency condition, craniotomy for removing intracranial lesions and clear hematoma can result in a chance of a successful delivery. Especially in the second and third trimesters of pregnancy, the management goal of anesthesia is to ensure the maternofetal safety and to maintain continuous pregnancy. Interventions: This article describes the process of intraoperative anesthesia management and maternal-fetal outcomes and discusses the key issues for the anesthesia management of cAVM rupture during pregnancy, including considerations of physiological changes during pregnancy and anesthesia medication, intraoperative monitoring, the maintenance of hemodynamic stability, and the control of intracranial pressure, among other considerations. Resection of intracranial lesions should be performed whenever possible while maintaining the pregnancy for better maternal and infant outcomes. Outcomes: The operations of the 3 pregnant women were successfully completed under our detailed anesthesia planning and careful anesthesia management. All the patients recovered well after the operation, and underwent cesarean section to give birth smoothly. Lessons: The preservation of pregnancy under cAVM resection is a complex challenge for anesthesiologists, and these 3 cases provide an extensive amount of experience for anesthesia management in similar situations. Detailed anesthesia planning and careful anesthesia management by anesthesiologists are important guarantees for good maternal and fetal outcomes.